2020
DOI: 10.1111/1365-2478.13011
|View full text |Cite
|
Sign up to set email alerts
|

Study the elastic properties and the anisotropy of rocks using different machine learning methods

Abstract: This paper aims to demonstrate that the elastic stiffnesses and the anisotropic parameters of rocks can be accurately predicted from geophysical features such as the porosity, the density, the compression stress, the pore pressure and the burial depth using relevant machine learning methods. It also suggests that the extreme gradient boosting method is the best method for this purpose. It is more accurate, extremely faster to train and more robust than the artificial neural networks and the support vector mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The XGB model, an advanced tree boosting system presented by Chen and Guestrin, 35 was confirmed to be a perfect machine-learning model for learning tabular datasets. 31,[36][37][38] It uses many additive functions f k to represent the relationship between the vector of input features X i and the output target y i of ith measurement as…”
Section: The Chosen Xgboost Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…The XGB model, an advanced tree boosting system presented by Chen and Guestrin, 35 was confirmed to be a perfect machine-learning model for learning tabular datasets. 31,[36][37][38] It uses many additive functions f k to represent the relationship between the vector of input features X i and the output target y i of ith measurement as…”
Section: The Chosen Xgboost Modelmentioning
confidence: 99%
“…35 XGBoost model is considered for the present study because it was confirmed to outperform other advanced machine-learning models for different types of tabular datasets. 31,[36][37][38] Also, the main objective of this study is not to repeat a comparison between different machine-learning tools but it focuses more on the data treatment strategy. More precisely, we aim to demonstrate that adding more low-cost and measurable features to the initial dataset would significantly improve the accuracy of the machine-learning model.…”
Section: The Chosen Xgboost Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Because of its ability to automate analytical models using training data with minimal human intervention, machine learning (ML) approach may be a good alternative for anisotropy estimation. Nguyen-Sy et al 9 utilized three machine learning models with Artificial Neural Network, Extreme Gradient Boosting and Support Vector Machine to predict transversely anisotropy elastic stiffnesses. These models incorporated porosity, density, compressional stress, pore pressure, and burial depth, all derived from core samples, as features to train and test the ML models.…”
Section: Introductionmentioning
confidence: 99%